1998
DOI: 10.1530/eje.0.1380302
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of erythropoietin secretion by continuous subcutaneous infusion of recombinant human GH in anemic patients with chronic renal failure

Abstract: We have investigated the effect of human GH on erythropoietin (EPO) secretion in eight anemic patients with chronic renal failure (CRF) (three males and ®ve females, aged from 46 to 83 years). Recombinant human GH was infused subcutaneously at a¯ow rate of 2 mg/kg body weight per 0.1 ml/h for 72 h using a portable infusion pump. Blood samples were obtained immediately before and 2, 4,6,12,24,36, 48, 60, 72, 84, 96, 108, 120 and 168 h after the start of GH infusion. Storage urine samples were obtained before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…24 Thus, FSH would be the first pituitary hormone able to increase Epo mRNA expression in in vitro conditions, although GH has been previously shown to stimulate Epo secretion in anemic patients with chronic renal failure. 25 These results, together with the previous description of specific binding sites in Leydig cells, suggest that Epo may play a yet unknown local regulatory role in testis. It is tempting to speculate that testis could respond to specific stimuli with an increased local production of Epo that would stimulate Leydig cell steroidogenesis or could act inside the seminiferous tubule.…”
Section: Resultssupporting
confidence: 60%
“…24 Thus, FSH would be the first pituitary hormone able to increase Epo mRNA expression in in vitro conditions, although GH has been previously shown to stimulate Epo secretion in anemic patients with chronic renal failure. 25 These results, together with the previous description of specific binding sites in Leydig cells, suggest that Epo may play a yet unknown local regulatory role in testis. It is tempting to speculate that testis could respond to specific stimuli with an increased local production of Epo that would stimulate Leydig cell steroidogenesis or could act inside the seminiferous tubule.…”
Section: Resultssupporting
confidence: 60%
“…EPO secretion is controlled mainly by oxygen pressure (Koury et al 1988, Eckardt et al 1989. We previously reported that plasma EPO levels increased after the start of rhGH infusion in anemic patients with chronic renal failure (Sohmiya et al 1998) and in adult patients with GH deficiency (Sohmiya & Kato 2001). Human plasma EPO levels increased within 6 h after the start of rhGH administration, suggesting that GH directly stimulates EPO production.…”
Section: Discussionmentioning
confidence: 99%
“…Although GH has a stimulatory effect on erythropoiesis, there have been few reports on the role of GH in EPO secretion. We previously reported that GH treatment increased plasma EPO levels in anemic patients with diabetic nephropathy (Sohmiya et al 1998) and in patients with GH deficiency (Sohmiya & Kato 2001). EPO is secreted from various organs depending on various conditions.…”
Section: Introductionmentioning
confidence: 99%
“…80 The fact that the rise in plasma Epo occurred earlier than the rise in insulin-like growth factor-1 (IGF-1) indicates that GH directly stimulates Epo production. IGF-1 was earlier shown to promote the growth of erythrocytic progenitors.…”
Section: Other Erythropoietic Hormonesmentioning
confidence: 99%